RESPONSE OF BROILER CHICKS TO DIETARY CARDAMOM (Elettaria cardamomum) AS A FEED ADDITIVE (Journal of Veterinary Medicine and Animal Production, 2022)
An experiment was carried out to study the response of broiler chicks to dietary cardamom (Elettaria cardamomum) as a natural feed additive on broiler performance and  blood parameters. A total of ninety six one-day old unsexed broiler chicks (Hubbard) were used. The birds were randomly divided into four equal groups each of 24 birds with four replicates (6 birds/replicate) in a completely randomized design. Four iso-nitrogenous and iso-caloric diets were formulated to meet nutrient requirements of broiler chicks as outlined by National research Council NRC .They were supplemented with four levels of cardamom (0.0%, 0.15%, 0.30% and 0.45%). The study lasted for six weeks. Parameters measured were feed intake, body weight gain, feed conversion ratio (FCR), pre-slaughter weight, dressing percentage and some blood parameters (glucose, total protein and total lipids). Results showed that the dietary cardamom supplementation had significantly (P
Keywords: Broiler Chicks; Cardamom